2019
DOI: 10.3389/fbioe.2019.00252
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Approaches to Inhibit Sialylation of Multiple Myeloma in the Bone Marrow Microenvironment

Abstract: Aberrant glycosylation modulates different aspects of tumor biology, and it has long been recognized as a hallmark of cancer. Among the different forms of glycosylation, sialylation, the addition of sialic acid to underlying oligosaccharides, is often dysregulated in cancer. Increased expression of sialylated glycans has been observed in many types of cancer, including multiple myeloma, and often correlates with aggressive metastatic behavior. Myeloma, a cancer of plasma cells, develops in the bone marrow, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 100 publications
(105 reference statements)
1
9
0
Order By: Relevance
“…These findings are consistent with a growing body of literature demonstrate the hypersialylation and increased expression of sialylated antigens in prostate, breast, bladder, and testicular cancer and malignancies in the bone marrow 79‐86 . Generally, there were many similarities between gynecological cancers and other cancers, whereas the type of sialyltransferases that are overexpressed varied per cancer type.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with a growing body of literature demonstrate the hypersialylation and increased expression of sialylated antigens in prostate, breast, bladder, and testicular cancer and malignancies in the bone marrow 79‐86 . Generally, there were many similarities between gynecological cancers and other cancers, whereas the type of sialyltransferases that are overexpressed varied per cancer type.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with a growing body of literature demonstrate the hypersialylation and increased expression of sialylated antigens in prostate, breast, bladder, and testicular cancer and malignancies in the bone marrow. 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 Generally, there were many similarities between gynecological cancers and other cancers, whereas the type of sialyltransferases that are overexpressed varied per cancer type. Using nanotechnology like surface‐enhanced Raman spectroscopy, sialic acid has been found in saliva, blood and cancer tissue of breast cancer patients, indicating its potential to be a highly sensitive and specific (noninvasive) biomarker for the screening of breast cancer in women.…”
Section: Discussionmentioning
confidence: 99%
“…that mediates important biological functions (10). It has been demonstrated that abnormal sialylation is closely associated with malignant brain tumors and multiple myeloma, and is usually accompanied by changes in the expression levels of sialyl transferases (STs) (11,12).…”
Section: St8sia1 Inhibits the Proliferation Migration And Invasion Of Bladder Cancer Cells By Blocking The Jak/stat Signaling Pathwaymentioning
confidence: 99%
“…erefore, interfering with sialylation may promote translational navigation of the milieu-drug resistance boundaries and define alternative combinatorial treatment strategies bringing sialylation inhibitors to the MM-stroma interface [30]. us, nanotechnologically engineered tools provided next-generation strategies for tailored anti-MM therapy by optimization of pharmacokinetics and pharmacodynamics profile of conventional chemotherapeutic agents [31].…”
Section: The Role Of the Bone Marrow Microenvironment: Novel Molecular Dependencies In Multiple Myelomamentioning
confidence: 99%
“…Currently, delivery systems employing the sialylation inhibitor 3Fax-Neu5Ac encapsulation in combination with BMA are intensively investigated, in order to potentially block MM homing and enhance drug efficacy as well. In frame of this thinking, Natoni et al [30] have shown that BMSCs can nurse MM by shaping an immune-tolerogenic milieu and uncovered sialylation as an actionable mechanism to boost the immune response [30].…”
Section: The Role Of the Bone Marrow Microenvironment: Novel Molecular Dependencies In Multiple Myelomamentioning
confidence: 99%